2018
DOI: 10.1002/qj.3244
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the CHIRPS satellite rainfall estimates over eastern Africa

Abstract: Long and temporally consistent rainfall time series are essential in climate analyses and applications. Rainfall data from station observations are inadequate over many parts of the world due to sparse or non‐existent observation networks, or limited reporting of gauge observations. As a result, satellite rainfall estimates have been used as an alternative or as a supplement to station observations. However, many satellite‐based rainfall products with long time series suffer from coarse spatial and temporal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
316
2
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(389 citation statements)
references
References 38 publications
22
316
2
9
Order By: Relevance
“…More generally TARCAT is amongst the best products in terms of rain event detection. As emphasized by Dinku et al () for East Africa, this may be explained by the fact that TARCAT uses local calibration to select cold‐cloud duration thresholds. At the interannual time‐scale, CHIRPS and TMPA perform best, although when compared against fully independent stations (southern Congo‐Brazzaville) PERSIANN has comparable skills. TARCAT has the lowest correlations with observations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More generally TARCAT is amongst the best products in terms of rain event detection. As emphasized by Dinku et al () for East Africa, this may be explained by the fact that TARCAT uses local calibration to select cold‐cloud duration thresholds. At the interannual time‐scale, CHIRPS and TMPA perform best, although when compared against fully independent stations (southern Congo‐Brazzaville) PERSIANN has comparable skills. TARCAT has the lowest correlations with observations.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies focused on a single African subregion or country, e.g. Uganda (Maidment et al , ; Diem et al , ; 2019), the Zambezi Basin (Cohen Liechti et al , ), West Africa (Gosset et al , ; ), Angola (Pombo et al , ), East Africa (Dinku et al , ), or the Ethiopian Rift Valley (Tesfamariam et al , ), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CHIRPS includes passive microwave estimates through the direct use of the monthly precipitation climatology CPHclim and in the CCD calibration phase [29]. It must also be mentioned that the next studies will benefit from the recently released version 3 of the TARCAT dataset, whose first results have been described in the literature [27,33]. Whilst maintaining its peculiarity concerning the exclusive use of a historical rain gauge dataset, several aspects regarding the calibration process were updated in this new version of TARCAT with the intent to fix known problems, i.e., the dry bias and the unrealistic spatial artefacts that originated from the use of rectangular calibration zones.…”
Section: Resultsmentioning
confidence: 99%
“…These aspects can introduce unwanted perturbations. In particular, the exploitation of simultaneous rain gauge measurements within the retrieval algorithms to be merged with the satellite estimates as in ARC2 and CHIRPS can insert inhomogeneities [33]. TARCAT makes use only of an historical rain gauge dataset for the calibration of IR brightness temperatures, and this mitigates the possible effects of the variations of rain gauge network density over time.…”
Section: Time Series Homogenizationmentioning
confidence: 99%
“…CHIRPS dataset was chosen because of the long‐term (1981 to present) and public domain data availability and the relatively high spatial and temporal resolutions, whereas the majority of the available global rainfall datasets have coarser resolutions (Table ). Moreover, Dinku () validated the CHIRPS dataset using reference rain gauge measurements from Ethiopia, Kenya, and Tanzania and reported that CHIRPS performed better than African Rainfall Climatology and Tropical Applications of Meteorology using Satellite data rainfall products over most of the Eastern Africa region.…”
Section: Methodsmentioning
confidence: 99%